Bioprospecção das espécies vegeTAIS Alternanthera brasiliana (L.) Kuntze E Fridericia platyphylla (Cham.) L. G. Lohmann para produção de bioenxertos em reparações ósseas - MORAIS, Camila Silva de (2021)
Bone defects often appear secondary to trauma, infection or the presence of tumors and for the repair of these various biomaterials they have been used effectively. The objective of this work was to evaluate the bone healing effect of grafts produced with chitosan gel associated with the crude extract of Alternanthera brasiliana (L.) Kuntze (terramicina) and Fridericia Platypylla L. (cipó-una) on bone healing after the production of experimental fractures in rats. Thus, a bone graft was made by incorporating the hydroalcoholic extracts of A. brasiliana and F. Platyphylla at 0.5% to a 2% chitosan gel. Bone failure was produced surgically in the middle third of the left radius of male Wistar rats (Rattus norvegicus), 100 days old, which were evaluated at 30, 60 and 90 days after fracture production in relation to their healing, for serological, histopathological (HE and picrosirius red) and radiographic analyzes. The animals were randomly divided into four experimental groups (12 animals / group): CN - negative control - chitosan gel; CP - positive control - bovine bone mineral graft (Lumina Bone® - fine powder 0.5); TER - graft from A. brasiliana; CIPO - F. Platyphylla graft. The animals were euthanized at 30, 60 and 90 days respectively. The CIPO AND TER graft increased serum FAO concentrations at 30 and 90 days of treatment, while in the CP and CN groups they maintained the enzymes at moderate levels, indicating early osteogenesis for the experimental treatment groups (TER and FAB) when compared to the control negative, directly influencing bone mineralization rates that were decreased in the serum of the CIPO and TER groups, showing greater deposition of this in the focus of the fracture, being recruited by alkaline phosphatase. Regarding radiological analysis, bone callus formation was earlier in animals treated with CIPO and TER graft similar to what occurred with positive control (CP), as well as the remodeling rates were excellent for experimental grafts, but with less expression of positive control. In the histological evaluation, it was noted that the positive and negative controls behaved as expected, and the TER group stood out with greater bone maturation during the healing periods and a greater amount of expressed collagen, followed by CIPO. Thus, the TER and CIPO treatment groups have promoted osteo-regeneration in a satisfactory manner, but further studies should be carried out to deepen their mechanisms of action.